Local Strain Distribution in ZnO Microstructures Visualized with Scanning Nano X‐Ray Diffraction and Impact on Electrical Properties. Issue 11 (2nd May 2021) - Jordt, Philipp; Hrkac, Stjepan B.; Gröttrup, Jorit; Davydok, Anton; Krywka, Christina; Wolff, Niklas; Kienle, Lorenz; Adelung, Rainer; Magnussen, Olaf M.; Murphy, Bridget M.
Abstract : The fast and contact‐free detection of biomagnetic vital signs can benefit clinical diagnostics in medical care, emergency services, and scientific studies, hugely. A highly sensitive magnetoelectric sensor for the detection of biomagnetic signals combined with the piezotronic effect is a promising path to increase the signal detection limit. Herein, the results of three ZnO microrods examined by nano X‐ray diffraction and current–voltage curves to investigate the crystalline structure influence on the Schottky contact properties are presented. The measurements reveal different strain distributions for the three rods and that these are linked with the electrical properties, showing that the crystalline quality has a direct influence on the Schottky contact properties. An analytical model is created to determine the influence of the stress. Although rotation of the strain orientation changes the strain appearance in the measurement, it does not affect the Schottky contact properties. Abstract : Three metal‐coated ZnO microrods are investigated with a combination of strain revealing nano X‐ray diffraction (XRD) and current–voltage curves. It is shown that the crystallite structure inside the microrods has a substantial impact on the electrical properties of the Schottky contact. Complementary, a strain distribution model is created to visualize the strain influence on the measurements.